1991
DOI: 10.1111/j.1751-1097.1991.tb01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Singlet Oxygen Formation Dominant in Triplet Quenching Processes? Measurement of the Quantum Yield of Singlet Oxygen Formation by the Time‐resolved Thermal Lens Method

Abstract: The quantum yields of singlet oxygen formation (ØΔ) by the quenching of triplet states of organic sensitizers are measured at various concentrations of the sensitizers by using the time‐resolved thermal lens method. Above a certain concentration, ØΔ is independent of the sensitizer concentration. Below the threshold, ØΔ gradually decreases as the concentration of the sensitizer decreases. The extrapolation of ØΔ to zero concentration indicates that singlet oxygen formation is not necessarily dominant in the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Recently, the surprising result that the 3' values for anthracene, 9,10-dibromoanthracene (DBA), and quinoxaline decrease very sharply at low concentrations of sensitizers was obtained by time-resolved thermal methods. 27 Decreasing the concentration of anthracene from 1.5 X 10"4 M to 1.5 X 10"5 M and of DBA from 1.7 X 10"4 M to 2 X 10"5 M was reported in ref 27 to decrease "1 by 20 and 32%, respectively. We checked these data by the time-resolved phosphorescence method.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, the surprising result that the 3' values for anthracene, 9,10-dibromoanthracene (DBA), and quinoxaline decrease very sharply at low concentrations of sensitizers was obtained by time-resolved thermal methods. 27 Decreasing the concentration of anthracene from 1.5 X 10"4 M to 1.5 X 10"5 M and of DBA from 1.7 X 10"4 M to 2 X 10"5 M was reported in ref 27 to decrease "1 by 20 and 32%, respectively. We checked these data by the time-resolved phosphorescence method.…”
Section: Resultsmentioning
confidence: 90%
“…Many studies and arguments have been aimed to explain the differences in S Δ values between π,π* and n,π* sensitizers, since most examined π,π* sensitizers have shown high values (0.8−1.0) 1,4,11,15 while n,π* aromatic ketones displayed low efficiencies (0.3−0.4). , There are now several examples of n,π*-excited states available for which high S Δ values have also been substantiated, in particular the bicyclic azoalkanes 1 and 2 16 and indanetrione 3 , all of which possess a pure n,π* configuration and are shown below. The S Δ values of the aliphatic ketones (Table ) and several aromatic n,π*-excited ketones in protic solvents are also quite high (0.5−0.7). 5a, These examples, along with many examples of π,π* states for which low efficiencies for singlet oxygen production have been observed, , demonstrate that a general correlation between efficiency for singlet oxygen production and the sensitizer electronic configuration does not exist.
…”
Section: Discussionmentioning
confidence: 98%
“…Since process 2a leads to the formation of singlet oxygen, O 2 ( 1 Δ g ), by energy transfer, many studies have been aimed to measure the efficiency for singlet oxygen production from triplet states ( S Δ ), which provides a measure for the relative contribution of process 2a. , Although it is expected that the S Δ values of a sensitizer increase with decreasing energy of the excited state 6a and decreasing charge-transfer (CT) character of the encounter complex or exciplex, these dependencies were not found to be universal. Despite earlier suggestions 5,6,15 that a π,π* triplet is required for highly efficient singlet oxygen formation, recent work demonstrates that the n,π* triplet states of bicyclic azoalkanes are very efficient sensitizers, while some π,π* states show low efficiencies. ,6a,, …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is now well-known that, for ketones with , * triplets, the probability of 02( 8) generation on collisonal quenching of the triplet (Sa) in benzene lies in the range 0.3-0.4, while for ketones with , * triplets, SA ~0.8-1.0. [1][2][3][4][5][6][7][8][9][10][11] The physical reasons for this effect probably have to do with the fact that excitation is localized on the carbonyl group for ketones with , * triplets. In ref 11, it was shown that a heavy atom in sensitizers with , * triplets slightly decreases SA values, whereas in bromo-substituted acetophenones, a sharp decrease in SA values was observed.…”
Section: Introductionmentioning
confidence: 99%